Agricultural policies and trade paths in Turkey - Larson, Donald; Martin, Will; Sahin, Sabnem; Tsigas, Marinos (Wiley, 2016)
In 1959, shortly after the European Economic Community was founded under the 1957 Treaty of Rome, Turkey applied for Associate Membership of the then six‐member common market. By 1963, a path for integrating the economies of Turkey and the eventual European Union had been mapped. As with many trade agreements, agriculture posed difficult political hurdles, which were never fully cleared, even as trade barriers to other sectors were eventually removed and a Customs Union formed. In this paper, we trace the influences the Turkey‐EU economic institutions have had on agricultural policies and the agricultural sector. Using an applied general equilibrium framework we provide estimates of what including agriculture under the Customs Union would mean for the sector and the economy. We also discuss the implications of fully aligning Turkey's agricultural policies with the EU's Common Agricultural Policy, as would be required under full membership.